Ocorrência e distribuição da subordem Hyperiidea (Crustacea : Amphipoda) para o Oceano Atlântico Sul Ocidental (02. - 40.S) - Lima, Marilene Carvalhal Gonçalves de (2001)
Study of the occurrence and distribution of the species of suborder Hyperiidea found in the area between 02º and 40°S, thus filling a gap in the Western South Atlantic Ocean, with bore scant work on the group. The four collections selected, comprising the Northeastern, Center, Southeastern and Southern areas, displayed an average density of 132.87 ind. l00m^-3. The FINEP XI collection, from the Southeast area was the most representative in density, reflecting its exclusive sampling in the coastal zone, where normally a great abundance of organisms is found. The greatest diversity and wealth of species was found at ocean stations. The study area, taken up by the tropical, subtropical and temperate zones, with the predominance of the oligotrophic tropical waters of the Brazil Current is limited, in the north by the equatorial region, and in the south by the Subtropical Convergence. One hundred and seven (107) species were identified in the two hundred and seventy-nine (279) samples studied, the most abundant species being Lestrigonus bengalensis Giles, Themisto gaudichaudii Guérin e Themisto australis (Stebbing), while Lestrigonus bengalensis, Brachyscelus crusculum Bate and Hyperietta vosseleri (Stebbing), were the species with the highest frequencies of occurrence. Lestrigonus bengalensis is pointedly the species responsible for the greatest abundance of the material studied. The second most abundant species, Themisto gaudichaudii, with occurrence only in the Southern area bears great representative and importance in the trophic chain of the temperate and polar regions. Fifteen (15) instances of associations between the Hyperiidea and gelatinous organisms of the salp and siphonophore types have also been found.